2022
DOI: 10.3389/fnagi.2022.911221
|View full text |Cite
|
Sign up to set email alerts
|

Association of Plasma and Electroencephalography Markers With Motor Subtypes of Parkinson’s Disease

Abstract: ObjectiveThe aim of this study was to investigate the correlations of plasma neurodegenerative proteins and electroencephalography (EEG) dynamic functional network (DFN) parameters with disease progression in early Parkinson’s disease (PD) with different motor subtypes, including tremor-dominant (TD) and postural instability and gait disorder (PIGD).MethodsIn our study, 33 patients with PD (21 TD and 12 PIGD) and 33 healthy controls (HCs) were enrolled. Plasma neurofilament light chain (NfL), α-synuclein (α-sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Other studies have also investigated the association of GFAP and NfL with cognition, albeit predominantly with screening tools of global cognition (e.g., Mini‐Mental State Examination [MMSE], MoCA), and have found elevated GFAP to be associated with worse baseline cognition or cognitive decline in AD/MCI, 10,47 PD or other synucleinopathies, 38 or FTD, 37,48 while others did not 10,49 . Similarly, studies have found elevated NfL to be associated with worse cognition or cognitive decline in AD/MCI, 8,10,42,50 PD or other synucleinopathies, 44–46,50–53 or FTD, 54 while others did not 10,47–49,53,55 …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also investigated the association of GFAP and NfL with cognition, albeit predominantly with screening tools of global cognition (e.g., Mini‐Mental State Examination [MMSE], MoCA), and have found elevated GFAP to be associated with worse baseline cognition or cognitive decline in AD/MCI, 10,47 PD or other synucleinopathies, 38 or FTD, 37,48 while others did not 10,49 . Similarly, studies have found elevated NfL to be associated with worse cognition or cognitive decline in AD/MCI, 8,10,42,50 PD or other synucleinopathies, 44–46,50–53 or FTD, 54 while others did not 10,47–49,53,55 …”
Section: Discussionmentioning
confidence: 99%